Financial integration in East Asia - De Brouwer, Gordon (Trade and development (Cambridge, England), 1999)
Financial Integration in East Asia by Gordon De Brouwer features important research assessing the theory and practice of financial integration and provides the first major study of the recent upheavals in East Asian financial markets and economies. This is the latest volume in the distinguished Cambridge series Trade and Development.